Factors Influencing Revisit Intention of Class B Hospital Patients in Jakarta - Sianita, Pricillia Priska; Harwani, Yuli; Permana, Dudi; Sofriana Imaningsih, Erna (Dinasti Publisher, 2024)
This research aims to build a new conceptual framework model which is novelty, which is a combination of models or concepts from previous research combined with the conditions of class B hospitals in Jakarta which makes it possible to develop Positive EWOM, Experience, Care Quality, Satisfaction conditions. Regarding the Revisit of Class B Hospital Patient Intentions in Jakarta in order to provide maximum class B Hospital services in Jakarta to patients so that they can continue to compete. Location This research will be carried out at a Class B Hospital in Jakarta. The selection of research locations was based on the number of Class B hospitals in Jakarta compared to other areas. The method used is a qualitative method to obtain hypotheses and conceptual frameworks.